Protective axis of the renin-angiotensin system in the brain - Gironacci, Mariela Mercedes (2014)
The RAS (renin-angiotensin system) is composed of two arms: the pressor arm containing AngII (angiotensin II)/ACE (angiotensin-converting enzyme)/AT1Rs (AngII type 1 receptors), and the depressor arm represented by Ang-(1-7) [angiotensin-(1-7)]/ACE2/Mas receptors. All of the components of the RAS are present in the brain. Within the brain, Ang-(1-7) contributes to the regulation of BP (blood pressure) by acting at regions that control cardiovascular function such that, when Ang-(1-7) is injected into the nucleus of the solitary tract, caudal ventrolateral medulla, paraventricular nucleus or anterior hypothalamic area, a reduction in BP occurs; however, when injected into the rostral ventrolateral medulla, Ang-(1-7) stimulates an increase in BP. In contrast with AngII, Ang-(1-7) improves baroreflex sensitivity and has an inhibitory neuromodulatory role in hypothalamic noradrenergic neurotransmission. Ang-(1-7) not only exerts effects related to BP regulation, but also acts as a cerebroprotective component of the RAS by reducing cerebral infarct size and neuronal apoptosis. In the present review, we provide an overview of effects elicited by Ang-(1-7) in the brain, which suggest a potential role for Ang-(1-7) in controlling the central development of hypertension.